2017
DOI: 10.1093/ejcts/ezw352
|View full text |Cite
|
Sign up to set email alerts
|

Perventricular device closure of perimembranous ventricular septal defect: effectiveness of symmetric and asymmetric occluders

Abstract: Perventricular device closure of pmVSDs appears safe and effective with symmetric and asymmetric occluders. However, the lower residual shunt disappearance and higher branch block incidence rates for asymmetric occluders would favour more proactive conversion to surgical repair immediately when residual shunt is present intraoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…[3][4][5][6] In view of its special advantages, as an effective supplementary therapy, transthoracic device closure of VSDs totally guided by TEE has been frequently used in China in recent years. [7][8][9][10] Compared to the two methods of device closure of VSDs, the core part of both methods is the use of an occluder, and the most remarkable difference between them is the establishment of different delivery tracks. The transcatheter method has no incision and quick recovery, but requires X-ray exposure and associated expensive machinery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6] In view of its special advantages, as an effective supplementary therapy, transthoracic device closure of VSDs totally guided by TEE has been frequently used in China in recent years. [7][8][9][10] Compared to the two methods of device closure of VSDs, the core part of both methods is the use of an occluder, and the most remarkable difference between them is the establishment of different delivery tracks. The transcatheter method has no incision and quick recovery, but requires X-ray exposure and associated expensive machinery.…”
Section: Discussionmentioning
confidence: 99%
“…The details of these two occluders have been well described in previous reports. [7][8][9][10] Operative technique All patients were administered general anesthesia and TEE with a 6T/9T multiplane probe by GE Vivid 7 (General Electric Company Corp., MA, USA) was used to identify the accurate size, morphological features, and visualization of the rims of the VSDs and particularly to evaluate the relationship between the defect and aortic valve. The maximal measured value of the VSD was used as the standard for the selection of the size of the occluder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the journal Gray et al report a hybrid technique in young infants: perventricular device closure (PVDC) which employs transcatheter techniques after heart is exposed through a mid‐sternotomy without cardiopulmonary bypass, atriotomy or ventriculotomy . Previous studies demonstrated that PVDC is a safe and effective procedure for VSD closure . Gray et al's observations support these finding and extend it to very small infants; median age and weight of their population were just 5.2 months and 5.1 kg.…”
mentioning
confidence: 98%
“…PVCD procedure represents a spectrum of techniques from totally percutaneous to one requiring median sternotomy. Gan et al reported 16 cases which were performed through a puncture hole in the chest wall and infundibulum of right ventricle . After closing the septum cardiac puncture site was also closed by a device.…”
mentioning
confidence: 99%